PEMIKIRAN TASAWUF FALSAFI AWAL: RABI’AH AL-‘ADAWIYYAH, AL-BUSTAMĪ, DAN AL-HALLAJ - Mubaidi Sulaeman (Refleksi: Jurnal Filsafat dan Pemikiran Keislaman, 2020)
Many researchers believe that the philosophical Sufism tradition in Islam only emerged in the sixth century Hijriah. Is that right? If it is explored in more depth, it will soon be found that this is not quite right because long before that, in the Islamic tradition there were already some thoughts of Sufism that tended to lead to philosophical Sufism. Among the philosophical ideas of Sufism that were born in this early period were mahabbah, Ilahiyyah, fana', ittihad, and Hulul. Therefore, in this paper the author tries to describe the initial philosophical Sufism thought  contained in the thoughts of three Sufi figures, namely Rabi'ah al-'Adawiyyah, alBustami, and al-Hallaj. By presenting the philosophical Sufism thought that exists in their works, this article shows that the philosophical Sufism tradition in Islam has emerged long before the sixth century Hijriah, as is often believed by many circles.